(3QSGdI aj JMOjO CeQGV GdYjf hJYQjaGJgGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3YOO CeQGV GdLaf JSYI hYTQhf Gdbed GdhQOfjN GdSdGb GdMcQ GdZdW GdOed s
(3BNQgG (B:s
(3GdRQbI , efgG WHjYjI hefgG YGQVI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B95 - (3U(B100s
(3gfGc Tc aj fSHI GdeNWhW ddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B104 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj edj (B(1538) s
Keywords: (3GdWHs